Isolation and Characterization of a Molybdenum-reducing and Methylene Blue-decolorizing Serratia marcescens strain KIK-1 in Soils from Nigeria (Bioremediation Science and Technology Research (e-ISSN 2289-5892), 2018)
Bioremediation of toxic compound in polluted environment is currently considered as the most economical and ecofriendly approach, particularly at a lower concentration of the toxicant, where other physicochemical techniques are ineffective. In this work, molybdenum-reducing bacterium with the capacity to decolorize various azo and triphenyl methane dyes independent of molybdenum reduction was isolated from contaminated soil. The bacterium reduces molybdate to Mo-blue optimally at pH between 5.8 and 6.5, temperature, between 34 and 37 oC, molybdate concentration between 10 and 25 mM and phosphate concentration, 5.0 mM. Glucose was the best electron donor supporting molybdate reduction followed by sucrose, maltose, trehalose, d-mannose, glycerol, d-mannitol, d-sorbitol, myo-inositol, d-adonitol and salicin in descending order. The absorption spectrum of Mo-blue produced was similar to other previous Mo-reducing bacteria, and closely resembles a reduced phosphomolybdate. About 78.1, 63.4, 45.5 and 17.8% of the molybdenum reduction in this bacterium was inhibited by 2 ppm mercury (ii), silver (i), copper (ii) and chromium (vi), respectively. The biochemical analysis resulted in a tentative identification of the bacterium as Serratia marcescens strain KIK-1. The ability of this bacterium to detoxify molybdenum and decolorize azo dye makes this bacterium an important tool for bioremediation.
Keywords: Molybdenum, Methylene blue, Serratia, Bioremediation, heavy metals